Influência de atributos físicos de solos na produtividade do algodão em Mato Grosso - Ramos, Pâmila Nayana Ferreira (2022)
Cotton is cultivated in several regions of Brazil and the world, standing out in the world agribusiness. The demand for cotton fiber has increased annually, but it has suffered considerable losses in production and fiber quality. In order to foresee new needs and anticipate technologies, the study analyzed the influence of the variability of soil physical attributes with variables of interest to cotton farming. Therefore, in chapter 1 we investigated the physical relationships of the soil through simple linear regression analysis using the JAMOVI software, which allowed us to quantitatively explain the influence of soil attributes on cotton seed and fiber production. Pearson's test showed that the variables clay, silt, macroporosity, microporosity, and total porosity showed a positive correlation for fiber and core production, and fiber and sand and density, respectively, showed negative collinearity for fiber and core and fiber production. The influence of soil physical attributes (clay, silt, sand, macroporosity, microporosity, total porosity and density) on PFC (coll, harvested form) and PF was explained through simple linear regression analysis, which allowed to identify the highest percentage estimated by the straight, and therefore the highest quality of the adjustment obtained for Total Porosity, while the lowest percentage was for Macroporosity for cotton seed production and fiber production. In the second chapter we tried to quantitatively explain the influence of physical attributes on fiber quality. The strength, fineness, length and maturity of the fiber were analyzed using the High Volume Instrument (HVI). The sample results were analyzed using simple linear regression to show the percentage of variance between the physical attributes of the soil and fiber quality. In Pearson's correlation in the fiber quality test, only the physical attributes of soil macroporosity, microporosity and silt were linearly correlated, for uniformity (UNF), determined that macroporosity represents a positive correlation and cotton fiber fineness (MIC) showed a correlation negative for silt and microporosity. Therefore, along the gradient, the simple linear regression test revealed significant differences between the percentages of statistical variances of soil variables in relation to fiber quality.